ASEAN's Role in Countering Global Terrorism Towards Strengthening the Implementation of Regional Security Policy: Peran ASEAN dalam Menangani Terorisme Global Menuju Penguatan Pelaksanaan Kebijakan Keamanan Regional - Safira Embun Insanidya; Utami Okta Khamsa; Rohadhatul Aisy (Universitas Negeri Semarang, 2024)
The threat of global terrorism has grown beyond national borders and become a strategic issue in international security, including in Southeast Asia. ASEAN as a regional forum and organization plays an important role in building collective cooperation among member states to tackle transnational acts of terrorism. This article discusses ASEAN cooperation in countering terrorism through instruments such as ACCT, ASEANAPOL, AMMTC, ASC, ARF to defense forums such as ADMM and ADMM-Plus. Using a normative legal approach and descriptive qualitative method, this research evaluates the effectiveness of regional security policy implementation, and identifies the main obstacles such as differences in national legal systems, the lack of integration of digital legal instruments, and attachment to the principles of non-intervention and consensus (ASEAN Way). The results of the study show that although ASEAN has various security cooperation institutions, actual coordination in cross-border law enforcement is still not optimal. Differences in views on criminal penalties, the absence of digital evidentiary standards, and the absence of regional-scale operational agencies are the main obstacles. However, the decline in terror attacks in Southeast Asia since 2019 reflects that cooperation in prevention and intelligence is starting to show results. To strengthen ASEAN's role in dealing with global terrorism, it is necessary to establish a regional counter-terrorism agency with technical authority, develop the ASEAN Model Criminal Code as a measure of criminal law harmonization, and strengthen institutions to be able to react to threats in a fast, integrated, and binding manner. With these steps, ASEAN can move from being just a dialog forum to becoming a key actor in creating a resilient and sustainable regional security system.